Musical experience prior to traumatic exposure as a resilience factor: a conceptual analysis - Fraile, Elodie; Gagnepain, Pierre; Eustache, Francis; Groussard, Mathilde; Platel, Hervé (Frontiers in Psychology, 2023)
Resilience mechanisms can be dynamically triggered throughout the lifecourse by resilience factors in order to prevent individuals from developing stress-related pathologies such as posttraumatic stress disorder (PTSD). Some interventional studies have suggested that listening to music and musical practice after experiencing a traumatic event decrease the intensity of PTSD, but surprisingly, no study to our knowledge has explored musical experience as a potential resilience factor before the potential occurrence of a traumatic event. In the present conceptual analysis, we sought to summarize what is known about the concept of resilience and how musical experience could trigger two key mechanisms altered in PTSD: emotion regulation and cognitive control. Our hypothesis is that the stimulation of these two mechanisms by musical experience during the pre-traumatic period could help protect against the symptoms of emotional dysregulation and intrusions present in PTSD. We then developed a new framework to guide future research aimed at isolating and investigating the protective role of musical experience regarding the development of PTSD in response to trauma. The clinical application of this type of research could be to develop pre-trauma training that promotes emotional regulation and cognitive control, aimed at populations at risk of developing PTSD such as healthcare workers, police officers, and military staffs.